Trabalhadores e trabalhadoras técnico-administrativos em educação na UFMG: relações raciais e a invisibilidade ativamente produzida - Yone Maria Gonzaga (2011)
The present work has the main objective of comprehending what it means to be a black male or female worker and a white male or female worker in the Federal University of Minas Gerais state (UFMG), Brazil, and in which sense these possible meanings were built during the life and work trajectories of the technical administrators that work there. Moreover, it seeks to analyze the trajectories of those workers before and after their entrance in the university, in order to verify if the ethnical and racial issues had any impact in their lives. The theoretical and methodological premises were those of the Oral History. As an instrument for data collection we chose to develop a questionnaire with the purpose of gathering a profile of the subjects of research, including their self-declared racial categories and whether or not they had any interest in taking part in the research. We have also made individual semi-structured interviews with 15 of the workers we had previously made contact with and that had declared themselves to be black, biracial or white. The research found the existence of an actively built invisibility regarding the technical administrators and their work inside the institution, and that this situation becomes more alarming when said workers are black or biracial. Those discoveries lead us to conclude that the UFMG, as a institution of public education, needs to develop strategies and academic and administrative policies for fight against social injustices and work, power and knowledge standards that were build upon racism and sexism, and those strategies need to aim not only students and teachers, but also, and more importantly, the technical administrators.